Determining Authorship & Ownership of Ai-Generated Work Under Indian Copyright Law - Aditi Bharti, Gagandeep Kaur, (European Economic Letters (EEL), 2024)
The judicial decision in DABUS case have stirred up an international debate over AI authorship. This article analyses the judicial decisions determining the legal status under intellectual property laws of the work generated by an artificial intel-ligence. Since the traditional concept of intellectual property protects the work generated by humans, proliferation of artificial Intelligence raises the need to re- define the status of personhood, inventorship, authorship and subject matter eligibility. The research is non- empirical, based on the judicial decisions on DABUS and Dreamwriter along with the in-ternational conventions. The paper explores the question whether the existing laws are sufficient to address the techno-logical advancements, and if not, then what might be the possible outcome.